Body image and depression in girls with idiopathic precocious puberty treated with gonadotropin-releasing hormone analogue - Min-Seon Choi (Annals of Pediatric Endocrinology & Metabolism, 2016)
PurposePrecocious puberty (PP) is associated with psychological and behavioral problems. This study aimed to evaluate the perception of body image and depression in girls with PP receiving gonadotropin-releasing hormone (GnRH) analogue therapy.MethodsFrom March to August 2013, 82 girls with PP receiving GnRH analogue therapy were enrolled. Height, weight, body mass index, and stages of pubertal development were assessed. Participants completed a series of questionnaires on their body image perception and pubertal self-assessment. The depression score was calculated using the Korean Kovacs' Children's Depression Inventory.ResultsThe patients perceived their body to be more obese than the controls did. The mean depression score did not differ between the patients and controls. The mean depression scores according to Tanner stages (1: prepubertal, 2: early pubertal, and 3–5: mid to late pubertal stage) by self-assessment were 5.2±3.6, 6.8±4.9, and 11.4±10.1 (P<0.05), respectively. The perception of overall body build and figure (%) and the mean depression scores in patients were: dissatisfied (25.6%, 9.7±7.8) and satisfied (74.4%, 5.5±3.4) (P<0.05). In multiple linear regression analysis, self-T3 (Tanner stage 3–5 by self-awareness) and dissatisfaction about overall body build and figure were found to significantly affect the depression score(P<0.05).ConclusionThe perception of pubertal status and satisfaction about height or weight are unrelated to objective physical findings. Patients with PP are prone to distorted perception about their body image and breast development. Such incorrect body image seems to contribute to depression score.